Do IFRS Adoption and Corporate Governance Increase Accounting Information Quality in Indonesia? - Firmansyah, Amrie; Irawan, Ferry (Accounting Analysis Journal, 2019)
This study aims to determine the effect of IFRS (International Financial Reporting Standard) adoption and Corporate Governance on the accounting information quality in Indonesia. Corporate Governance in this study is represented by institutional ownership, independent commissioners and audit committees. The object of research is 77 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The regression method applied in the form of panel data with a period for six years (2009 - 2015). After conducting a model selection test, the chosen model is the fixed effect model (FEM). Based on the test results it is known that IFRS adoption, independent commissioners, and audit committees are not associated with the information accounting information quality, while institutional ownership is positively associated with the accounting information quality. From these results, it turns out that the adoption of IFRS on Indonesia Statement of Financial Accounting Standards (hereinafter referred to as PSAK) does not provide choices that could be utilized by managers to be able to improve the quality of financial statements. Meanwhile, institutional ownership could have a role in improving the monitoring function of company managers. Furthermore, the fact that the presence of independent commissioners still could not improve the monitoring function of managers to improve the accounting information quality. Likewise, the audit committee does not prove to have a supervisory function for managers in preparing in high-quality financial statements.